2017
DOI: 10.1103/physrevb.96.125402
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the photoemission distribution of strongly interacting two-dimensional overlayers

Abstract: Photoemission tomography (PT), the analysis of the photoemission intensity distribution within the plane wave final-state approximation, is being established as a useful tool for extracting the electronic and geometric structure of weakly interacting organic overlayers. Here we present a simple method for extending PT, which until now has been based on the calculations of isolated molecules. By including the substrate and a damped plane-wave final state, we are able to simulate the photoemission intensity dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 56 publications
1
37
0
Order By: Relevance
“…4d) demonstrates that its orbital structure suffers only minor changes upon adsorption, despite the former LUMO being filled and involved in the bonding of the molecule to the metal. A similar robustness of molecular orbitals has been demonstrated for a number of π -bonded systems 2123,35 .…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…4d) demonstrates that its orbital structure suffers only minor changes upon adsorption, despite the former LUMO being filled and involved in the bonding of the molecule to the metal. A similar robustness of molecular orbitals has been demonstrated for a number of π -bonded systems 2123,35 .…”
Section: Resultssupporting
confidence: 65%
“…Evidently, we need to consider the patterns of the combined adsorbate/substrate system including the local bonds at the edges in order to determine the precise chemical nature of the surface intermediate. We employ here a recently developed extension of PT in which the momentum map simulations are no longer based on gas phase molecular orbitals, but on the wave functions of the (strongly) interacting molecule/metal interface 35 .…”
Section: Resultsmentioning
confidence: 99%
“…It would be advantageous to substantiate this interpretation by simulations of momentum maps for benzene interacting with Pd(110) rather than benzene in the gas phase, that is, by using the wave functions of the benzene/Pd(110) interface as intitial states in the simulation of the photoemission intensity. We have demonstrated that this may indeed improve the agreement with measured momentum maps [60][61][62]. For molecule/metal interfaces with considerable interactions, however, in the present case such simulations are hampered by the fact that the DFT electronic structure has a severe shortcoming.…”
Section: Discussionmentioning
confidence: 62%
“…Moreover, the fact that the experimental MM of π 2 appears much sharper in the k [001] -direction than the simulated MM may aslo originate from molecule-substrate interaction. Not only does it lead to energetically broadened molecular resonances, but it also causes an enhanced intermolecular band dispersion which in turn results in substructures and sharper features in constant-binding energy momentum maps [60][61][62].…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, orbital tomography has emerged as an exciting extension of the photoemission technique for imaging localized electronic wave functions in thin film molecules [5][6][7][8][9] . In this framework, the photoemission process can be described either in a one-step model where the final state is represented by a plane wave or using more sophisticated final state approximations [10][11][12][13] . Although the phase of the electronic wave function is not an observable, it can be retrieved under suitable experimental conditions 14 , or by use of iterative algorithms traditionally employed in coherent diffraction imaging 15,16 .…”
Section: Introductionmentioning
confidence: 99%